LITERASI NASABAH DALAM PENGAMBILAN KEPUTUSAN PEMBIAYAAN PADA BANK SYARIAH INDONESIA KC JENGGOLO: CUSTOMER LITERACY IN FINANCING DECISION MAKING AT BANK SYARIAH INDONESIA KC JENGGOLO - Mubarok, Muhammad Dzulfahmi; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2024)
Customer literacy in financing decision-making at Islamic banks is an important aspect that customers must possess in the financing decision-making process. This research aims to determine the level of literacy possessed by customers of Shariah banks, specifically focusing on the case study of financing customers at Bank Syariah Indonesia KC Jenggolo in making financing decisions. The approach and method used in this research are qualitative descriptive approach and case study method. Based on the research results, it can be concluded that financing customers of Bank Syariah Indonesia KC Jenggolo do not yet have adequate literacy regarding the financing available at Bank Syariah Indonesia in several aspects when customers make financing decisions. The results of this research can be used by banks as a fact in the field regarding the importance of literacy regarding financing and the fact that there are still customers who have poor literacy regarding the financing they have taken.